B Cell Orchestration of Anti-tumor Immune Responses: A Matter of Cell Localization and Communication - Kinker, Gabriela Sarti; Vitiello, Glauco Akelinghton Freire; Ferreira, Wallax Augusto Silva; Chaves, Alexandre Silva; Cordeiro de Lima, Vladmir Cláudio; Medina, Tiago da Silva (Frontiers in Cell and Developmental Biology, 2021)
The immune system plays a crucial role in cancer development either by fostering tumor growth or destroying tumor cells, which has open new avenues for cancer immunotherapy. It was only over the last decade that the role of B cells in controlling anti-tumor immune responses in the tumor milieu has begun to be appreciated. B and plasma cells can exert anti-tumor effects through antibody-dependent cell cytotoxicity (ADCC) and activation of the complement cascade, even though their effector functions extend beyond the classical humoral immunity. In tumor tissues, B cells can be found in lymphoid aggregates, known as tertiary lymphoid structures (TLSs), a well-organized non-encapsulated structure composed of immune and stromal cells. These structures reflect a process of lymphoid neogenesis occurring in peripheral tissues upon long-lasting exposure to inflammatory signals. The TLS provides an area of intense B cell antigen presentation that can lead to optimal T cell activation and effector functions, as well as the generation of effector B cells, which can be further differentiated in either antibody-secreting plasma cells or memory B cells. Of clinical interest, the crosstalk between B cells and antigen-experienced and exhausted CD8+ T cells within mature TLS was recently associated with improved response to immune checkpoint blockade in melanoma, sarcoma and lung cancer. Otherwise, B cells sparsely distributed in the tumor microenvironment or organized in immature TLSs were found to exert immune-regulatory functions, inhibiting anti-tumor immunity through the secretion of anti-inflammatory cytokines. Such phenotype might arise when B cells interact with malignant cells rather than T and dendritic cells. Differences in the spatial distribution likely underlie discrepancies between the role of B cells inferred from human samples or mouse models. Many fast-growing orthotopic tumors develop a malignant cell-rich bulk with reduced stroma and are devoid of tertiary lymphoid structures, which highlights the importance of carefully selecting pre-clinical models. In summary, strategies that promote TLS formation in close proximity to tumor cells are likely to favor immunotherapy responses. Here, the cellular and molecular programs coordinating B cell development, activation and organization within TLSs will be reviewed, focusing on their translational relevance to cancer immunotherapy.